Hvězdy za železnou oponou - Jirásek, Pavel (Czech Republic, 2014)
A documentary about western popular music as bearer tendencies of democracy and freedom in the Czechoslovak area in period 1965 - 1990. Unique and comprehensive view of the cultural and political significance visits of western popular and alternative culture personalities who were brought to the former socialist Czechoslovakia. The documentary is accompanied by archive and contemporary interviews with Manfred Mann, Justin Hayward, Die Toten Hosen, Suzi Quatro, Joan Baez or members of the Rolling Stones. Through exclusive historical footage are illustrated significant cultural events
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films